Adult T-cell leukemia/lymphoma complicated by Pneumocystis pneumonia in a non-endemic area. (2023) - Kunimoto, Mayu; Inomata, Minoru; Chin, Haruka; Ito, Yu; Fujimoto, Kazushi; Muto, Yutaka; Nomura, Moe; Sato, Kota; Sakamoto, Keita; Awano, Nobuyasu; Kuse, Naoyuki; Kumasaka, Toshio; et al.
Abstract: Adult T-cell leukemia/lymphoma (ATLL) is a human T-cell leukemia virus type 1-inducing unevenly-distributed T-cell malignancy, which is often complicated by opportunistic infections. Here, we discuss the case of a 75-year-old woman presenting with Pneumocystis pneumonia (PCP) who was subsequently diagnosed with ATLL in Tokyo, a non-endemic area of ATLL. In addition to the elevated soluble interleukin-2 receptor and the detection of flower cells in the screening blood test, the high-resolution computed tomography findings, atypical of PCP, were clues to the diagnosis of ATLL. ATLL should be considered as an underlying disease when patients present with PCP, even in non-endemic areas.